Coaching for the development of athlete self-esteem: The relationship between the self-perceptions of junior cricketers and their perceptions of coaching behaviour - Paterson, G. D. (1999)
The need to identify self-esteem development as an explicit objective in youth sport has received some attention during the past decades. This study explored the relationship between the self-perceptions of cricketers aged 13-15 years (N=222) and their perceptions of their coaches' application of 10 instructional strategies. Data collection included: (a) pre- and post-season (10 weeks) measures of players' self-esteem using Harter's (1985) Self-Perception Profile for Children; (b) pre- and post-season measures of players' cricket self-perceptions, affective outcomes derived from cricket participation, and cricket motivation orientation using a cricket-specific adaptation of Klint's (1988) affect inventory; and (c) players' post-season perceptions of their coaches' application of 10 coaching strategies using an inventory designed by the author. Pearson product moment correlations (r) were used to measure the strength and direction of the relationships between the variables (Vincent, 1995). Results revealed: (a) significant correlations between dimensions of self-esteem, cricket self-perceptions and the affective outcomes of pride, excitement and happiness, and (b) significant correlations between the cricketers' perceptions of their coaches application of the instructional strategies and dimensions of their post-season self-esteem, cricket self-perceptions, affective outcomes and intrinsic motivation orientation. These findings provide further insights for coaches seeking to develop athlete self-esteem on the sports field.